Belize 2026 - Bartlett, Ray; Ferrarese, Marco, 1980-; Chanona, Carolee; Harding, Paul; Kaminski, Anna (Lonely Planet, 2025)
"Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime to Belize. Discover popular and off the beaten track experiences from chasing waterfalls on a boat tour to Vaca Lake, to spotting noisy black howler monkeys in the wild at the Community Baboon Sanctuary, and diving and snorkelling at the most remote of Belize's Caribbean cayes, far-flung Glover's Reef"--Publisher's description.